Gender Stereotypes in Slovakia and Portugal - Mihalcova, Bohuslava; Gontkovicova, Barbora; Koraus, Antonín; Lukac, Jozef; Javorcik, Patrik (Journal of Ecohumanism, 2024)
The aim of the article is to compare selected indicators of gender equality investigated in the Slovak Republic and allegedly currently published in Portugal. This intention resulted from the previous cooperation of the authors with Portuguese colleagues in the given field. An important part of this article will also concern the conducted research study, which focuses on the investigation of gender differences in managerial positions. We will search an employment in managerial positions in terms of gender and the amount of salary for managerial work done at the same level. Work experience in a managerial position, regardless of its level and industry, will be a condition of the research. The research sample consists of randomly selected managers of a selected region of various countries. An instrumentalism is a questionnaire survey with subsequent statistical processing. The form we use is an electronic form and disseminated through social networks in such a way that the anonymity of the respondents is fully preserved. The mentioned research study will present one of the possible approaches to the investigation of the issue of gender differences in managerial positions.